2011
DOI: 10.1002/adfm.201100493
|View full text |Cite
|
Sign up to set email alerts
|

Gecko‐Inspired Dry Adhesive for Robotic Applications

Abstract: Most geckos can rapidly attach and detach from almost any kind of surface. This ability is attributed to the hierarchical structure of their feet (involving toe pads, setal arrays, and spatulae), and how they are moved (articulated) to generate strong adhesion and friction forces on gripping that rapidly relax on releasing. Inspired by the gecko's bioadhesive system, various structured surfaces have been fabricated suitable for robotic applications. In this study, x–y–z asymmetric, micrometer‐sized rectangular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
133
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 132 publications
(140 citation statements)
references
References 29 publications
(13 reference statements)
2
133
0
Order By: Relevance
“…The 1X flaps showed no measurable adhesion (F ad < 0.1 mN) to the silica surface which is consistent with our previous work ( Figure 4). 11 The graph of apparent area, A app vs the normal actual load, F ⊥ P for the 1X flaps showed no hysteresis between the loading and unloading curves (Figure 4), which is a characteristic signature of nonadhesive contact. This observation is attributed to the high surface roughness (RMS roughness ≈ 250 nm) of the top edge of the 1X flaps (as visualized in the SEM) that reduces the real area of contact between the flaps and the spherical silica surface.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The 1X flaps showed no measurable adhesion (F ad < 0.1 mN) to the silica surface which is consistent with our previous work ( Figure 4). 11 The graph of apparent area, A app vs the normal actual load, F ⊥ P for the 1X flaps showed no hysteresis between the loading and unloading curves (Figure 4), which is a characteristic signature of nonadhesive contact. This observation is attributed to the high surface roughness (RMS roughness ≈ 250 nm) of the top edge of the 1X flaps (as visualized in the SEM) that reduces the real area of contact between the flaps and the spherical silica surface.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The full details of the force measurements have been described in previous work. 10,11 As a summary, the spherical glass disc was mounted to the top friction device, which can slide laterally over a distance of 100500 μm at different sliding speeds (110 μm/s). The PDMS flaps were glued to a flat glass disc, which sits on a double cantilever spring with strain gauges that can measure the normal forces.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using this property, they demonstrated sliding of a clean glass surface against and along the tilted microfibres without applying any external normal force and strong anisotropy for shear stresses was observed [17]. Friction and adhesion forces for tilted rectangular flaps were also investigated by Yu et al The structures were found to have strong friction and adhesion forces when sliding along the tilt direction, and low friction and adhesion forces when sliding against the tilt direction [18]. However, these artificial adhesives with inclined micropillars demonstrated a relatively lower magnitude of interfacial friction and adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous methods and processes have been reported in literature to emulate this particular anisotropic adhesion produced using inclined micropillar arrays [16][17][18][19][20]. Jin et al studied adhesion and friction properties of micropillar samples at various tilt angles and found that the tilt angle of the micropillars can lead to significant anisotropic friction.…”
Section: Introductionmentioning
confidence: 99%